Catechol versus carboxyl linkage impact on DSSC performance of synthetic pyranoflavylium salts - Pinto, Ana Lucia (2022)
co-financed by the ERDF under the PT2020 Partnership Agreement (POCI-01-0145-FEDER - 007265). FCT/MCTES is acicnowledged for Project PTDC/QEQ-QFI/1971/2014, grants PD/BD/135087/2017 (ALP), SFRH/BD/136556/2018 (VG) and a research FCT contract (LC).